Detecting the spatial quantum uncertainty of bosonic systems - Chille, Vanessa; Treps, Nicolas; Fabre, Claude; Leuchs, Gerd; Marquardt, Christoph; Aiello, Andrea (New Journal of Physics, 2016)
We present the quantum theory of direct detection of bosonic particles by multipixel detectors. For the sake of clarity, we specialize on beams of photons, and we study the measurement of different spatial beam characteristics, as position and width. The limits of these measurements are set by the quantum nature of the light field. We investigate how both, detector imperfections and finite pixel size affect the photon counting distribution. An analytic theory for the discretized detection setup is derived. We discuss the results and compare them to the theory presented by Chille et al 2015 Opt. Express 23 32777, which investigates the beam width noise independently of the measurement system. Finally, we present numerical simulations that furnish realistic and promising predictions for possible experimental studies.
CRIS-Team Scopus Importer:2022-06-05
Keywords: bosonic systems; quantum uncertainty; spatial measurements